Terpenes and Terpenoids Conjugated with BODIPYs: An Overview of Biological and Chemical Properties - Stanková, Jarmila; Jurášek, Michal; Hajdúch, Marián; Džubák, Petr (Journal of natural products, 2024)
Advancements in small-molecule research have created the need for sensitive techniques to accurately study biological processes in living systems. Fluorescent-labeled probes have become indispensable tools, particularly those that use boron-dipyrromethene (BODIPY) dyes. Terpenes and terpenoids are organic compounds found in nature that offer diverse biological activities, and BODIPY-based probes play a crucial role in studying these compounds. Monoterpene-BODIPY conjugates have exhibited potential for staining bacterial and fungal cells. Sesquiterpene-BODIPY derivatives have been used to study sarcoplasmic/endoplasmic reticulum calcium ATPase (SERCA), indicating their potential for drug development. Owing to their unique properties, diterpenes have been investigated using BODIPY conjugates to evaluate their mechanisms of action. Triterpene-BODIPY conjugates have been synthesized for biological studies, with different spacers affecting their cytotoxicity. Fluorescent probes, inspired by terpenoid-containing vitamins, have also been developed. Derivatives of tocopherol, coenzyme Q10, and vitamin K1 can provide insights into their oxidation-reduction abilities. All these probes have diverse applications, including the study of cell membranes to investigate immune responses and antioxidant properties. Further research in this field can help better understand and use terpenes and terpenoids in various biological contexts.
Keywords: molekulární struktura; fluorescenční barviva; Molecular Structure; Fluorescent Dyes; sloučeniny boru; Boron Compounds; lidé; terpeny; Terpenes; Humans